Implementation of Mikhmon Server for Qos Optimization and Traffic Control on Mikhmon Hotspot Network at Amicom Net - Husen, M.Hasan Amir; Firmansyah, Firmansyah (Universitas Ahmad Dahlan, 2025)
The increasing demand for stable and fair internet access, particularly on public networks like hotspots, presents challenges in maintaining Quality of Service (QoS) and ensuring balanced traffic distribution. This study aims to implement and evaluate the effectiveness of the Mikhmon Server as a solution for user management and traffic control on the Mikrotik hotspot network at AMICOM NET. A quantitative experimental approach was used by comparing network performance before and after the implementation of Mikhmon. Key QoS parameters measured include latency, throughput, and bandwidth fairness. Mikhmon, a web-based tool for managing Mikrotik users, enables administrators to set speed limits, distribute bandwidth evenly, and monitor user sessions in real-time. The results indicate a significant improvement in traffic management efficiency, with average latency reduced by 52.63% and more equitable bandwidth distribution among users. These findings demonstrate that Mikhmon is a practical and cost-effective tool for optimizing medium-scale hotspot networks.